Protein adsorption onto monoliths: A surface energetics study. Issue 3 (29th November 2017) - Aasim, Muhammad; Hidayatullah Khan, Muhammad; Bibi, Noor Shad; Zaman Khan, Nadir
Abstract: This part of work was done to explore the basic understanding of the adsorption chromatography by determining the interaction of selected model proteins ( n = 5) to monolithic chromatographic materials, with varying densities of butyl and phenyl ligands. Surface energetics approach was applied to study the interaction behavior. The physicochemical properties of the proteins and monolithic chromatographic materials were explored by contact angle and zeta potential values. These values were used to study protein to monolith interaction under various operating conditions. Surface energetics approach allowed the calculation of interaction energy as a function of distance, i.e. energy minimum values. Calculations were performed at various conditions to analyze the effect of major operating parameters on the interaction strength. The interaction strength exposed the hydrophobic nature of the monoliths which increases with increasing ligand density. Further, interaction energy of proteins were higher with monolith with butyl ligand compared to monolith with phenyl ligand. For instance, lactoferrin interaction to monoliths with butyl represents more interaction, i.e. 24.38 kT as compared to monoliths with phenyl i.e. 23.28 kT, keeping lambda as 0.2 nm and salt concentration as 100 mM of ammonium sulphate. Hence, more energy and time will be consumed for elution of proteins immobilized to monoliths with butyl. Similarly, the effect of solid surface for proteins immobilization, effect of ligand density and effect of lambda showed some interesting insights on the interaction behavior. The knowledge generated from the present work will help in the basic understanding as well as development of an efficient, low cost downstream processing design and may mimic the real chromatographic experiments.